Predictors of diarrheal mortality and patterns of caregiver health seeking behavior in in Karachi, Pakistan - Qamar, Farah Naz (J Glob Health, 2016)
BACKGROUND: Pakistan is unfortunately among the five countries that contributed to the most deaths due to diarrhea and pneumonia in 2010. To explore factors associated with diarrheal deaths we assessed care–seeking behavior and other predictors of diarrhea–related mortality in children in selected low–income peri–urban communities of Karachi, Pakistan. METHODS: A mixed methods study (qualitative and quantitative) using matched case–control design and focus group discussions with parents of children with moderate to severe diarrhea (MSD) was undertaken. Cases were children  <5 years of age who died within 60 days of developing an episode of MSD. Controls were age–matched children who survived after 60 days of an episode of MSD. Demographic, clinical, and care–related behavioral predictors of mortality were assessed. Conditional logistic regression was performed, matched adjusted odds ratios (mOR) are reported. RESULTS: Parents of 77 cases and 154 controls were interviewed. Cases were less likely to receive appropriate care compared to controls (mOR = 0.2, 95% confidence interval (CI) 0.05–0.91). Refusal for hospital admission (OR = 8.9, 95% CI 2.6–30.8), and delays in reaching the health facility (OR = 3.6, 95% CI 1.0–12.9) were significant independent predictors of mortality. We found strong beliefs in traditional and spiritual healing in the population; use of both modern and traditional/spiritual treatments concurrently was common. CONCLUSION: Appropriate care seeking behavior predicts survival in children with diarrhea in Pakistan. There is a complex belief system relating to traditional and standard therapies. Health education for appropriate health care seeking should be implemented in order to achieve a substantial decline in diarrheal disease mortality in Pakistan.